Variability in Benthic Exchange Rate, Depth, and Residence Time Beneath a Shallow Coastal Estuary. Issue 3 (8th March 2018) - Russoniello, Christopher J.; Heiss, James W.; Michael, Holly A.
Abstract: Hydrodynamically driven benthic exchange of water between the water column and shallow seabed aquifer is a significant and dynamic component of coastal and estuarine fluid budgets. Associated exchange of solutes promotes ecologically important chemical reactions, so quantifying benthic exchange rates, depths, and residence times constrains coastal chemical cycling estimates. We present the first combined field, numerical, and analytical modeling investigation of wave‐induced exchange. Temporal variability of exchange was calculated with data collected by instruments deployed in a shallow estuary for 11 days. Differential pressure sensors recorded pressure gradients across the seabed, and up‐ and down‐looking ADCPs recorded currents and pressures to determine wave parameters, surface‐water currents, and water depth. Wave‐induced exchange was calculated (1) directly from differential pressure measurements, and indirectly with an analytical model based on wave parameters from (2) ADCP and (3) wind data. Wave‐induced exchange from pressure measurements and ADCP‐measured wave parameters matched well, but both exceeded wind‐based values. Exchange induced by tidal pumping and current‐bed form interaction—the other primary drivers in shallow coastal waters were calculated from tidal stage variation and ADCP‐measured currents. Exchange from waves (mean = 20.0 cm/d; range = 1.75–92.3 cm/d) greatly exceeded exchange due to tides (mean = 3.7 cm/d) and current‐bed form interaction (mean = 6.5 × 10 −2 cm/d). Groundwater flow models showed aquifer properties affect wave‐driven benthic exchange: residence time and depth increased and exchange rates decreased with increasing hydraulic diffusivity (ratio of aquifer permeability to compressibility). This new understanding of benthic exchange will help managers assess its control over chemical fluxes to marine systems. Key Points: Measurements of differential pressure and wave parameters can be used to estimate wave‐driven benthic exchange in the field Wave‐induced benthic exchange rates exceeded current and tide‐induced rates by over an order of magnitude in a shallow estuary Numerical model shows hydraulic diffusivity and wave parameters control wave‐induced benthic exchange rate, depth, and residence time